Linguistic Study of some Uzbek Ethnographisms Expressing Wedding Ceremonies (International Journal of Psychosocial Rehabilitation, 2020)
The article gives a brief overview of ethnolinguistics, and it also gives information about some features of ethnographisms related to wedding ceremonies in the Surkhandarya province. Particularly, the names of wedding ceremonies and linguoculturologic symbols reflected in the bride's welcoming ceremony are analyzed.